Metabolic adaptation of the clam Ruditapes philippinarum during air exposure and the positive effects of sodium nitroprusside pretreatment - Zheng, Zhilong; Huo, Zhongming; Huang, Kaiyue; Jiang, Min; Yan, Xiwu; Liu, Yang; Qin, Yanjie (Frontiers in Physiology, 2023)
Manila clam (Ruditapes philippinarum), as one of the shellfishes living in the intertidal zone, is known for their strong ability to withstand air exposure. Sodium nitroprusside (SNP), as a donor of NO, has been shown to be useful for antioxidant and immune regulation in aquatic animals. In this study, an untargeted metabolomics (LC-MS/MS) technique was employed for the first time in Manila clam to analyze the metabolic and histological impacts after air exposure and the positive effects of SNP pretreatment. During air exposure, a large rise in taurine, L-glutamate and several polyunsaturated fatty acids (PUFAs) in clams has been detected, which indicated that clams may experience inflammatory reactions, oxidative stress, and an increase in blood ammonia content.When clams were exposed to SNP for 6 hours, Arginine, Spermine, L-Glutamic acid, and glutathione content were all up-regulated, indicating that the SNP exposure induced the production of NO and improved antioxidant capacity in clams. When the clams were exposed into air after SNP pretreatment, there were no significant differences in levels of taurine, L-glutamate and aliphatic acids between the experimental group and the control group. Gill tissue was seriously destroyed in clams directly exposed into air than those suffered from air exposure after SNP pretreatment, especially in those clams exposed into air for a long time (72h). Both metabolomics and tissue section structure indicated that SNP pretreatment decreased the stress responses caused by air exposure in R. philippinarum. These findings provided fresh insights and a theoretical foundation for the tolerance to air exposure and physiological functions of SNP (or NO) in R. philippinarum.